The Preliminary Study of Liquefaction Susceptibility Map in the Yogyakarta-Bawen Toll Road Sections I and II, Indonesia - Paulus Kevin; Muhrozi Muhrozi (Civil Engineering Dimension, 2023)
The parts of Yogyakarta-Bawen Toll Road Indonesia, based on the geological agency’s liquefaction susceptibility map are located on moderately susceptible to liquefaction soil. This map can be a preliminary indication of liquefaction as it can roughly indicate liquefaction potential. However, it cannot illustrate the actual condition in detail as its inputs are macro parameters (geological and seismicity factors). The existence of silty sand and sand, earthquake sources, and shallow groundwater increase the liquefaction possibility to occur in this important national project. Therefore, the Liquefaction Severity Index (LSI) and the Liquefaction Potential Index (LPI) using Sonmez’s and Iwasaki’s analysis methods are conducted with peak ground acceleration (PGA) of 0.322 g for the first section and in the second section 0.298 g. The results of the three types of analysis have relatively similar trends but the differences are in each category. The LSI’s categories are very low-moderate in the observed location, meanwhile, the LPI’s categories are low-very high.